2019
DOI: 10.1021/acsapm.9b00735
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Methacrylate-Grafted P(VDF-CTFE) and Albumin Layers for Reducing Fibrinogen Adsorption

Abstract: The use of extracorporeal devices is growing rapidly for the treatment of the fatal cardiovascular and kidney failures. Even though there has been much clinical progress in the past few decades to reduce fatality, these improvements are insufficiently supported by the development in medical devices. Particularly, it is imperative that the blood-contacting medical devices have nonprotein-fouling materials that can efficiently prevent blood coagulation. Herein, perfluoromethyl methacrylates (PFMMAs) with short p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The experimental F/C ratios of NFtB-19.7, −38.1, −57.4, and −77.3 were similar to or lower than the corresponding theoretical values, which indicated similar surface occupancies of carbon and fluorine atoms or rather the formation of carbon-enriched surfaces. It has been reported that functional groups with lower surface energies prefer to be located at the surface–air interface rather than inside the polymer film. ,,, Particularly, linear fluorocarbon chains have a strong tendency to migrate toward the surface due to their extremely lower surface energies . The F/C ratios of the films of P­(MMA–HFBMA) copolymers with linear fluorocarbon tails (−CF 2 CF 2 CF 3 ) in the HFBMA unit were indicative of fluorine-enriched compositions over the whole range of copolymer ratios (Figure S5).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The experimental F/C ratios of NFtB-19.7, −38.1, −57.4, and −77.3 were similar to or lower than the corresponding theoretical values, which indicated similar surface occupancies of carbon and fluorine atoms or rather the formation of carbon-enriched surfaces. It has been reported that functional groups with lower surface energies prefer to be located at the surface–air interface rather than inside the polymer film. ,,, Particularly, linear fluorocarbon chains have a strong tendency to migrate toward the surface due to their extremely lower surface energies . The F/C ratios of the films of P­(MMA–HFBMA) copolymers with linear fluorocarbon tails (−CF 2 CF 2 CF 3 ) in the HFBMA unit were indicative of fluorine-enriched compositions over the whole range of copolymer ratios (Figure S5).…”
Section: Resultsmentioning
confidence: 92%
“…It has been reported that functional groups with lower surface energies prefer to be located at the surface−air interface rather than inside the polymer film. 7,20,49,50 Particularly, linear fluorocarbon chains have a strong tendency to migrate toward the surface due to their extremely lower surface energies. 51 The F/C ratios of the films of P(MMA−HFBMA) copolymers with linear fluorocarbon tails (−CF 2 CF 2 CF 3 ) in the HFBMA unit were indicative of fluorine-enriched compositions over the whole range of copolymer ratios (Figure S5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation